The National Terminology Services: A New Paradigm - Jordaan-Weiss, Milde (Lexikos, 1995)
The new dispensation in South Africa necessitated a paradigm shift at the National Terminology Services (NTS). Being part of the Central Government, the NTS has to implement policy as laid down by the government of the day. Former policy, processes and products are described as well as the vision and objectives for the future. The NTS plays a vital role in the implementation of the Reconstruction and Development Program, as no communication is possible without terminology and no development or empowerment can take place without communication. The NTS has the infrastructure and knowledge to facilitate the development of the indigenous South African languages. Problems originating from the implementation of multilingual terminography are discussed, as well as strategies being implemented to overcome them. Finding a new Terminology Management System able to handle the documentation of the 11 official languages has high priority. As the client base of the NTS has broadened with the addition of more official languages, products have to be adapted, changing terminology needs have to be taken into account, and the accessibility of terminology has to be improved. The NTS hopes to contribute towards the promotion of mutual scientific and technical communication in South Africa in this way.